FOOT ANTHROPOMETRY OF ADULT BANGLADESHI MALE MEDICAL STUDENTS - M TANVEER HOSSAIN PARASH; HUMAIRA NAUSHABA; SADIA CHOUDHURY SHIMMI (International Journal of Pharma and Bio Sciences, 2016)
Anthropometrical data are required for developing a standard for a product, identifying a victim of a crime or accident, studying a civilization and also for treating patients. There is a paucity of anthropometric data of foot of adult Bangladeshi male. This study was carried out on 120 male students of Sir Salimullah Medical College, Dhaka. Foot length, foot width, heel breadth, instep and ball circumference of right and left foot, measured by slide caliper and flexible measuring tape, were 25.30 (± 1.24) cm and 25.32 (± 1.22) cm, 9.83 (± 0.64) cm and 9.85 (± 0.66) cm., 5.78 (± 0.67) cm and 5.64 (± 0.66) cm, 24.22 (± 1.38) cm and 24.08 (± 1.37) cm and 24.59 (± 1.48) cm and 24.40 (± 1.50) cm respectively. This study would provide the direction to construct baseline data of foot anthropometry of Bangladeshi people of different age groups and sexes.